1994
DOI: 10.1104/pp.105.3.891
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endogenous Abscisic Acid in Potato Microtuber Dormancy

Abstract: Potato (Solanum tuberosum L. cv Russet Burbank) microtubers generated in vitro from single-node explants contained substantial amounts (approximately 250 pmol/g fresh weight) of free abscisic acid (ABA) and were completely dormant for a minimum of 12 weeks. Microtubers that developed in the presence of 10 NM fluridone (FLD) contained considerably reduced amounts (approximately 5-25 pmol/g fresh weight) of free ABA and exhibited a precocious loss of dormancy. lnclusion of exogenous racemic ABA in the FLD-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 15 publications
2
70
0
2
Order By: Relevance
“…Consistently, subsequent studies showed that ABA levels are highest in deeply dormant tubers and decline during storage (Korableva et al 1980;Biemelt et al 2000;Destefano-Beltran et al 2006b). In addition, treatment of microtubers with the ABA biosynthesis inhibitor fluridone reduced the ABA content significantly which was accompanied by a shortened dormancy period (Suttle and Hultstrand 1994). Fig.…”
Section: Hormonal Controlmentioning
confidence: 88%
See 1 more Smart Citation
“…Consistently, subsequent studies showed that ABA levels are highest in deeply dormant tubers and decline during storage (Korableva et al 1980;Biemelt et al 2000;Destefano-Beltran et al 2006b). In addition, treatment of microtubers with the ABA biosynthesis inhibitor fluridone reduced the ABA content significantly which was accompanied by a shortened dormancy period (Suttle and Hultstrand 1994). Fig.…”
Section: Hormonal Controlmentioning
confidence: 88%
“…Abscisic acid is required for both initiation and maintenance of tuber dormancy (Suttle and Hultstrand 1994). The significance of ABA as dormancy-related hormone was first recognised by Hemberg (1949).…”
Section: Hormonal Controlmentioning
confidence: 99%
“…Suttle (1995) monitored ABA in tubers of one cultivar under three storage regimes. Even though in other studies the sustained presence of ABA was considered essential for the induction and maintenance of tuber dormancy (Suttle and Hultstrand, 1994), breaking of dormancy could not be attributed to the decline in ABA below a threshold level (Suttle, 1995). He concluded that other interna1 processes or factors were responsible for the loss of dormancy under natural conditions (Suttle, 1995).…”
Section: Other Evidence On Aba and Tuber Dormancymentioning
confidence: 96%
“…Evidence for a causal relationship between traits such as ABA content and potato dormancy has usually been based on correlative evidence from observations or treatments within a single genotype (Ji and Wang, 1988; Presence of More than One QTL per Chromosome Cvikrová et al, 1994;Suttle and-Hultstrand, 1994). As noted by Lebreton et al (1995), identifying the location of…”
Section: Coincidence With Qtls For Other Traitsmentioning
confidence: 99%
“…ABA is considered to be the principal dormancy- inducing agent. For various seeds and buds, it has been shown that ABA plays a role in dormancy development (Hole et al, 1989;Suttle and Hultstrand, 1994). Furthermore, young bulblets were very sensitive to the hormone (Djilianov et al, 1994).…”
Section: Discussionmentioning
confidence: 99%